Preparation of Mo-impregnated mordenite catalysts for the conversion of refined kernel palm oil into bioavtur - Trisunaryanti, Wega; Triyono; Wijaya, Karna; Kartini, Indriana; Purwono, Suryo; Rodiansono; Mara, Ady; Budiyansah, Amsal (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2023)
The research aims to study the effects of Mo metal embedded on H-Mordenite on its activity and selectivity of hydrodeoxygenation (HDO) for Refined Palm Kernel Oil (RPKO) into bioavtur. The RPKO was obtained from the results of degumming and bleaching process of palm kernel oil and then analyzed using Gas Chromatography-Mass Spectrometer (GC-MS). The impregnation of Mo metal was carried out by spraying using an ammonium heptamolybdate precursor solution ((NH4)6Mo7O24•4H2O) with an initial Mo metal content of 5, 10, and 15wt% of H-Mordenite to produce 5-Mo/Mor, 10-Mo/Mor, and 15-Mo/Mor. The 15-Mo/Mor catalyst produced the highest amount of liquid product (46.08wt%) with bioavtur yield of 43.19wt%. The usability test showed that 15-Mo/Mor catalyst still produced a good performance after three times of use in the RPKO feed HDO with the second and third run test liquid product of 34.82 and 46.14wt% respectively with bioavtur yield of 32.58 and 43.45wt%, respectively.